Economic analysis of corn second crop in response to doses and sources of nitrogen - Afonso, André Luis Gimenes; Cabral Filho, Fernando Rodrigues; Andrade, Christiano Lima Lobo de; Silva, Edson Cabral da (Brazilian Journal of Science, 2023)
Fertilization is one of the most relevant conditions to increase maize productivity, with the patient being the crop that absorbs the most nutrients from food. Most of the nitrogen fertilizers used in Brazil are water soluble and release quickly, which can be absorbed by plants and easily lost. Conventional urea is the most used source of water due to its higher concentration of high N2 and lower cost, but it has losses due to volatilization. The use of controlled-release fertilizers has been proposed to reduce losses, synchronize nutrient release with crop demand and increase the recovery efficiency of nutrients applied to the soil. In this sense, the objective of this work was to evaluate the economic viability of using different doses and travel sources in the off-season corn crop. The test was treated in the experimental area by the company Pulveriza Soluções Agrícolas, in the city of Rio Verde – GO, Brazil. Corn was sown on 01/29/2022, using a 5-row seeder with a horizontal disc seed distribution system. The experimental design used was randomized blocks, analyzed in a 5 x 2 + 1 factorial scheme, with 4 replications, totaling 40 experimental plots. Grain productivity per hectare increased as the fuel doses applied increased, regardless of the source.